Tinjauan Nutrigenomik - Angeline Fanardy (Cermin Dunia Kedokteran, 2020)
Nutrigenetik dan nutrigenomik didefinisikan sebagai ilmu yang mempelajari efek variasi genetik terhadap respons diet dan peranan nutrien serta bioaktif yang terkandung di dalam makanan. Tujuan nutrigenomik adalah menentukan kesesuaian nutriome (contohnya kombinasi asupan nutrien) dengan status genome (contohnya genom yang diturunkan atau didapat), sehingga dapat memelihara genom, ekspresi gen, metabolisme, dan fungsi sel. Nutrigenomik memberikan interpretasi data yang lebih baik atas studi intervensi epidemiologi dan klinis dampak kesehatan makanan yang dapat membantu memperbaiki rekomendasi nutrisi personal. Nutrigenetic and nutrigenomic are defined as studies of the effects of genetic variation on dietary responses and the role of nutrients and bioactive ingredients in foods in gene expression. The purpose of nutrigenomic is for nutriome nutrient adjustment (eg. combination of nutrient intake) with existing genomic status (derived or acquired genome contour) to maintain genome, gene expression, metabolism and cell function. Nutrigenomic provides a better interpretation of data from epidemiological and clinical intervention studies on the health effects of dietary factors to help improve personalized nutrition recommendation.